(untitled) (Al-Aasar, 2025)
Among the social activities promoted during the Prophet’s era, public welfare measures are of great importance in Islamic development and growth. And all the social activities related to manners, from which a good society grows, are attributed to Islam and the founder of Islam, Sayyidna Muhammad. Always promoted during his blessed tenure. It strengthened community bonds and unity, fostered a sense of belonging and support, provided a platform for socialization and networking, encouraged collective worship and spiritual growth. Promoted economic equality and justice. If we think from a historical point of view, we will know that ever since man has gained consciousness in human society there have been forces of good and evil, in knowledge and ignorance, in progress and decline, in justice and oppression, in collective There is a struggle between the good and the monopoly. For the first time in human history, the Holy Prophet (peace and blessings of Allah be upon him) started a global social revolution in the name of Islam under the guidance of Allah Almighty, which was the pioneer of progress in every field of human activities. Secondly, since the Muslim Ummah is a good Ummah, it has given a lot to humanity in every aspect of life. This is a nation that has been holding the status of kindness in every field. On the front of public welfare, the Muslim Ummah has given the world such bright ways that the light and effects of Islam are prominent to a large extent and the interpretation of Islam is as clear as day. The Prophet himself laid an organized and coherent foundation for public welfare, clarified the objectives, enacted legislation and implemented it in practice. Tent - It is undeniable that the concept of the first welfare state in the world also begins with the beloved person of the Prophet, peace be upon him. Every person who has a heartache feels a heart attack. Public welfare includes the establishment of Bait Al-Mal, charity, and the establishment of a social organization to collect and distribute Zakat, aid to widows, orphans and children, and promotion of education and learning, etc. Studying and practical implementation of all these aspects is the most important need of the time in the current era as well - public welfare was highly recorded in the actions and sayings of the Messenger of Allah, which cannot be denied by any intellectual and thinker. These aspects of the Prophet’s era highlight the importance of community building and development, literary development and public welfare in Islamic society.